Are monetary unions more synchronous than non-monetary unions? - Patrick M. Crowley; Christopher Trombley (Bank of Finland, 2015)
Within currency unions, the conventional wisdom is that there should be a high degree of macroeconomic synchronicity between the constituent parts of the union. But this conjecture has never been formally tested by comparing sample of monetary unions with a control sample of countries that do not belong to a monetary union. In this paper we take euro area data, US State macro data, Canadian provincial data and Australian state data — namely real Gross Domestic Product (GDP) growth, the GDP deflator growth and unemployment rate data — and use techniques relating to recurrence plots to measure the degree of synchronicity in dynamics over time using a dissimilarity measure. The results show that for the most part monetary unions are more synchronous than non-monetary unions, but that this is not always the case and particularly in the case of real GDP growth. Furthermore, Australia is by far the most synchronous monetary union in our sample.
URN:NBN:fi:bof-201508041349
Keywords: C49; E32; F44; F45; F62; 330